2022
DOI: 10.1123/iscj.2021-0010
|View full text |Cite
|
Sign up to set email alerts
|

Real Versus Ideal: Understanding How Coaches Gain Knowledge

Abstract: In an ever-evolving society, sport coaches are presented with a number of avenues through which they can acquire and refine their coaching knowledge. The purpose of this research was to replicate and extend past research to gain an up-to-date understanding of how coaches are presently gaining knowledge. This was done through a constructive replication using a sequential explanatory mixed-method design. Study 1 included 798 coaches who completed an online questionnaire detailing their use of 16 sources of coach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…This concurs with the accepted literature related to experiential leaning, whereby understanding, competency, proficiency, and expertise are extended beyond traditional educational formats (i.e. formal qualifications/official accreditation, and non-formal learning such as small courses and workshops), by specifically working and reflecting on in-situ, on-the-job, settings, contexts, and practical application (Author, 2018b;Erickson et al, 2008;Miettinen, 2000, Van Woezik, et al, 2021.…”
Section: Benefits Of Qualifications and Extended Learning Preferencessupporting
confidence: 85%
See 1 more Smart Citation
“…This concurs with the accepted literature related to experiential leaning, whereby understanding, competency, proficiency, and expertise are extended beyond traditional educational formats (i.e. formal qualifications/official accreditation, and non-formal learning such as small courses and workshops), by specifically working and reflecting on in-situ, on-the-job, settings, contexts, and practical application (Author, 2018b;Erickson et al, 2008;Miettinen, 2000, Van Woezik, et al, 2021.…”
Section: Benefits Of Qualifications and Extended Learning Preferencessupporting
confidence: 85%
“…advisory systems and mentoring); and also incidental learning -which takes place as a by-product of other activities, such as social interaction and observing others, and is unintentional, yet a positive influence (Author, 2018b). Whilst the benefit of mentoring, informal learning opportunities, and work placed practice does hold true across most coaching contexts (for instance, Chapman et al, 2019;Leeder et al, 2022, Sawiuk et al, 2018, and Van Woezik, et al, 2021, in the findings outlined in this paper the processes seem to be particularly helpful and effective. Indeed, and specific to the learning context of youth/community football coaches, the results here strongly concur with those of Hertting ( 2019), who stated that flexibility and mentoring systems/informal learning were best suited to complement a framework of mandatory education.…”
Section: Benefits Of Qualifications and Extended Learning Preferencesmentioning
confidence: 78%
“…Coach education research has widely indicated that coaches acquire knowledge through formal, nonformal, and informal means (Mallett et al, 2009;Nelson et al, 2006). Although some studies suggest that informal sources have greater learning value (Culver et al, 2019;Koh, Bloom, et al, 2014;Maclean & Lorimer, 2016;Van Woezik et al, 2021), other studies contend that both nonformal (e.g., Armour, 2010) and formal (Araya et al, 2015;Vella et al, 2013) sources have merit as well. The main argument that informal sources of learning have greater impact on a coaches' knowledge is that it addresses the unique coaching issues relevant to a coach's context (Cushion et al, 2010).…”
mentioning
confidence: 99%
“…The main argument that informal sources of learning have greater impact on a coaches' knowledge is that it addresses the unique coaching issues relevant to a coach's context (Cushion et al, 2010). For example, communities of practice sessions appreciate coach learning as a social process (e.g., Stoszkowski & Collins, 2014;Van Woezik et al, 2021) that allows the cocreation of knowledge and sharing of experiences that would be applicable to the coaches' practice within their context (Culver et al, 2019). Key benefits of communities of practice reported by coaches were that they provided them the opportunity to network with more experienced coaches, to acquire knowledge from others that was more relevant to improve athlete performance in their context, and to hone their interpersonal and intrapersonal coaching knowledge during interactive and reflective activities (Araya et al, 2015;Culver et al, 2019).…”
mentioning
confidence: 99%
“…13 Coach education on how to generate positive development is an important factor for positive outcomes to occur. 27,28 Coach development and education may occur through many forms, such as by informally learning from other coaches, being a mentor or being mentored, coaching, and formally by engaging in coach courses and programs (e.g., Taylor et al; 30 Van Woezik et al; 31 Walker et al 32 ). Although the branch of research on coach training and practices has blossomed, research within the context of disability sport remains understudied.…”
mentioning
confidence: 99%